Revaluating “Germany’s worst street”. Commercial gentrification on Leipzig’s Eisenbahnstraße? - Hübscher, Marcus; zur Lage, Felix; Ertle, Läticia; Briem, Kathrin; Brucker, Nadine (DIE ERDE – Journal of the Geographical Society of Berlin, 2021)
Leipzig’s Eisenbahnstraße in Germany is currently discussed from different points of view. Ethnicity, crime, but also urban growth and revaluation processes are in the center of the discourse. As one of the city’s high streets, the Eisenbahnstraße and its two surrounding quarters show changes in the commercial structure, which are claimed to be gentrification processes. This paper aims to analyze both the process by using the concept of commercial gentrification and its local perception. This is done by mapping current commercial uses in the retail, service and gastronomy sector, categorizing them, and comparing them to secondary data. Apart from that, local stakeholder’s perspectives are evaluated based on 16 structured interviews conducted with shop owners on the one hand, and a survey among 105 passersby on the street on the other hand. The material indicates that the Eisenbahnstraße is currently in an initial phase of commercial gentrification. This is displayed by diversification of supply and demand structures, represented by the arrival of new potential customers, but also by a diversification of business concepts. Apart from that, commercial activities experience a strong increase in the area and have led to spatial dispersion from the high street to neighboring roads. We argue that Leipzig’s Eisenbahnstraße follows partially the East German gentrification path, as until now no displacement is identified, but the case also stands out due to the important role of ethnicity in commercial structures.